Locus equations and the place of articulation for the Latvian sonorants - Taperte, Jana (Baltistica, 2014)
In the article, the sonorant consonants of Standard Latvian are investigated using locus equations. The aim of the study is to examine whether locus equations can be considered as efficient descriptors of consonantal place of articulation both within the group of sonorants and across different manner classes in Standard Latvian.Two-type sequences were analyzed: (1) the CV part of isolated nonsense CVC syllables, where C is one of the sonorants [m; n; ɲ; l; ʎ; r] and V is one of the vowels [i(ː); e(ː); æ(ː); ɑ(ː); ɔ(ː); u(ː)]; (2) the V(ː)C part of isolated nonsense V(ː)CV (VCV for [ŋ]) structure utterances, where C is one of the nasals [m; n; ɲ; ŋ] and V is one of the vowels [i; e; æ; ɑ; ɔ; u]. Each utterance was recorded in three repetitions by every of 10 native Latvian speakers (five males and five females), thus 3420 items were analyzed in total. Statistical analysis of locus equation slopes and y-intercepts both for the sonorants and for the whole consonant inventory of Standard Latvian was performed in order to test the relevance of these indices for discriminating places of articulation across different manner classes.By plotting the data for the whole consonant inventory in slope-by-intercept space it is possible to distinguish between the groups of palatals/dentals/alveolars and labials/velars, while the results of statistical analysis show significant difference among all place categories. According to the results, there are certain coarticulatory mechanisms associated with particular places of constriction for the Latvian consonants that allow linking locus equation data to different place categories, although they are also affected by manner and voicing. Nevertheless, place of articulation as a determinant of coarticulatory patterns overrules these factors when other possible influences are excluded.